Suicidal Ideation vs. Suicide Attempts: Clinical and Psychosocial Profile Differences Among Depressed Patients. Issue 5 (May 2017) - Lewitzka, Ute; Spirling, Sina; Ritter, Dirk; Smolka, Michael; Goodday, Sarah; Bauer, Michael; Felber, Werner; Bschor, Tom
Abstract : Abstract: This study investigated whether personality traits, psychopathological characteristics, and sociodemographic factors in depressed patients differentiate patients with only suicidal thoughts from those who have attempted suicide. We investigated two groups of patients with an affective disorder: 198 patients with a suicide attempt within the last 3 months (sex ratio male to female, 1:1.3; mean age male to female, 44.8/44.7 years) and 30 patients without a suicide attempt but with suicidal thoughts (sex ratio male to female, 1:2; mean age male to female, 39.4/42.6 years) using a comprehensive measurement (Mini-International Neuropsychiatric Interview, Structured Clinical Interview for DSM-4 Axis II disorders, Hamilton Depression Scale, Beck Depression Inventory, State-Trait Anxiety Inventory, Hamilton Anxiety Scale, Brief Psychiatric Rating Scale, Clinical Global Impression Scale, Beck-Hopelessness Scale, Scale for Suicide Ideation, Impulsivity Rating Scale, Barratt Impulsivity Scale, Inventory for the Assessment of Aggression Factors, State-Trait Anger Expression Inventory, Ways of Coping Checklist). Several differences distinguished the two groups, namely, in personality traits such as anxiety or coping strategies and sociodemographics ( e.g., education level). Personality traits, psychopathological characteristics, and sociodemographic factors are useful tools for assessing suicidal risk. Our findings encourage us to suggest that clinicians pay particular attention to sociodemographic variables such as separation/divorce and a lower education level when conducting risk assessments on suicidal patients.